Pengaruh Profitabilitas Dan Leverage Terhadap Nilai Perusahaan Pada Sektor Property Dan Real Estate Di Indonesia - Yusuf Faisal; Egi Gumala Sari (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2024)
Purpose – This study aims to determine and analyze the effect of profitability and leverage on company value in property and real estate companies. Design/methodology/approach – The method used in this study uses quantitative methods by sampling using purposive sampling techniques with the results of 27 property and real estate sector companies listed on the Indonesia Stock Exchange in 2012-2021. The data used is secondary data, which is data obtained directly in the form of financial statements from www.idx.co.id website. Data analysis techniques are carried out using statistical analysis, namely: classical assumption test, multiple linear analysis, and hypothesis test, as well as the coefficient of determination with SPSS 25 Findings – Based on the results of the study, it was found that profitability has a positive and significant effect on company value, and leverage has a positive and significant effect on company value in the property and real estate sector. Research limitations/implications – This research is expected to provide information related to income quality and provide benefits in making the right decision